Society 5.0 sebagai Bagian dari Kontribusi Warga Wilayah Pesisir (Studi Kasus: Mangunharjo, Semarang) - Fithor, Alin; Nugroho, Beni Sabdo; Baihaqi, Ahmad Fauzan; Meilala, Bryna Rizkinta Sembiring (Ideas Publishing, 2025)
Mangunharjo Beach, Semarang, is not just a beach, but there are residents who contribute to every development that combines natural beauty, the latest technology, and the spirit of mutual cooperation, this beach is transformed into a living laboratory to realize the concept of Society 5.0. The purpose of this study is to determine the extent of the scientific renewal of the Mangunharjo community. The study was conducted by analyzing field surveys of groups of people who were carried out randomly. With the contribution of the community, coastal cities, community concerns and community pressure, In addition to the digitalization of smart cities, this location inspires to create a better future, technology is not just a tool, but also a bridge to connect humans and nature.